Culture of Honor and Attitudes Toward Intimate Partner Violence in Latinos - Dorothee M. Dietrich; Jessica M. Schuett (SAGE Open, 2013)
Adherence to culture of honor is examined in relationship to attitudes toward intimate partner violence (IPV) in Latinos. Prior research suggests that high honor culture adherence may be associated with more tolerance for IPV. In the present study, Latino participants ( N = 72) completed questionnaires on culture of honor and attitudes toward various aspects of IPV, including attitudes toward the violence itself, toward the perpetrator, toward the victim, and toward victim help-seeking. High and low reputation threat conditions were depicted in vignettes of IPV to manipulate for honor adherence. Findings suggest that participants who adhere more greatly to culture of honor are more accepting of IPV, more approving of the perpetrator, and less approving of seeking help.